2021
DOI: 10.5114/nan.2021.108028
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in patients recently recovered from coronavirus disease (COVID‑19)

Abstract: Aim of the study:To evaluate the presence and severity of anxiety and depressive symptoms in patients who recently recovered from coronavirus disease 2019 . Material and methods: In this cross-sectional observational study, patients who had recovered from COVID-19 were assessed between February and April 2021. The symptoms reported by patients were evaluated using a questionnaire developed by the authors based on the National Institute for Health and Care Excellence (NICE) guidelines. The Beck Depression Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Six studies used univariate analysis to identify risk factors for depression [16,18,20,21,24,25]. Being female was associated with depression in four studies [16,20,21,24].…”
Section: Risk Factors For Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies used univariate analysis to identify risk factors for depression [16,18,20,21,24,25]. Being female was associated with depression in four studies [16,20,21,24].…”
Section: Risk Factors For Depressionmentioning
confidence: 99%
“…Six studies used univariate analysis to identify risk factors for depression [16,18,20,21,24,25]. Being female was associated with depression in four studies [16,20,21,24]. In contrast, studies by Menges et al [22] and Grover et al [34] found that there were not any correlations between sex and depression.…”
Section: Risk Factors For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial heterogeneity across studies was observed in each of the three meta-analyses (I 2 =98.8%, 97.4% and 95.9%, respectively; p<0.001). ASADI-POOYA [24] AUL [91] AYDIN [65] BALDINI [62] FERNÁNDEZ-DE-LAS-PEÑAS [105] SUÁREZ-ROBLES [128] DARCIS [101] DREYER [103] ZAYET [137] YOMOGIDA [34] VENTURELLI [135] VARGHESE [134] TAYLOR [131] TAWFIK [14] SZEKELY [66] SULTANA [129] STAVEM [127] SONNWEBER [58] RIGHI [123] PELUSO [13] O'SULLIVAN [122] O'KEEFE [121] NAIK [54] MOTIEJUNAITE [64] MECHI [44] MALLIA [115] KLEIN [111] GABER [106] EROL [25] DIAZ-FUENTES [102] DANKOWSKI [100] CARFI [96] CORTÉS-TELLES [69] CARVALHO-SCHNEIDER [97] BOARI [94] VIJAYAKUMAR [65] Total (I 2 =95.9%, p<0.001) ZHANG [39] D'CRUZ [35] D'CRUZ [35] TODT [132] TAYLOR [131] SKJORTEN [38] DAYNES [10] APARISI [26] DE GRAAF [61] YIN …”
Section: Prevalence Of Post-covid Breathlessness Among Covid-19 Survi...mentioning
confidence: 99%
“…The influential analysis indicated no single study had a major impact on the pooled prevalence estimate (supplementary table 3). [63] BALDINI [62] BELL [92] DARCIS [101] CARFI [96] CARVALHO-SCHNEIDER [97] CORTÉS-TELLES [59] DANKOWSKI [100] DIAZ-FUENTES [102] DREYER [103] EROL [25] GABER [106] GALVÁN-TEJADA [19] ÇALIK KÜTÜKCÜ [95] BOARI [94] MORADIAN [117] MEIJE [56] MAHMUD [114] LANDI [112] JACOBS [109] KLEIN [111] MALLIA [115] COMEBAC STUDY GROUP [85] MOTIEJUNAITE [64] GHOSN [11] GARRIGUES [53] FORTINI [36] BLOMBERG [93] ARNOLD [89] AUGUSTIN [90] ARMANAGE [88] SUÁREZ-ROBLES [128] VIJAYAKUMAR [65] VARGHESE [134] VENTURELLI [135] Subtotal (I 2 =97.8%, p<0.001) Heterogeneity between groups: p=0.014 ZHAO [138] TOSATO [133] SZEKELY [66] TAWLIK [14] TAYLOR [131] SUN [130] SHOUCRI [126] SULTANA [129] STAVEM [127] SONNWEBER ...…”
Section: Prevalence Of Post-covid Breathlessness Among Covid-19 Survi...mentioning
confidence: 99%